2021
DOI: 10.3127/ajis.v25i0.3223
|View full text |Cite
|
Sign up to set email alerts
|

"Humanized Robots": A Proposition of Categories to Understand Virtual Influencers

Abstract: Worldwide investments in influencer marketing are growing and could reach US$ 101 billion in 2020. But how can the brands shield themselves from scandals and other limitations of human influencers? The solution for many companies has involved robots. Virtual influencers (VI) are virtual robots that can emulate human appearance and behaviour and have become a trend in marketing. This study analyses how non-human influencers affect marketing communication by adopting two methods that are unpublished in the inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…A systematic literature review was conducted to identify the current state of knowledge, evaluate the existing literature, and identify further research directions in the field of VIs. A previous (and only one, to the best of our knowledge) systematic literature review on the issue of CGIs and their use in the marketing field identified 32 scientific articles, of which only two referred to nonhuman VIs (da Silva et al, 2021). A systematic literature review follows well‐defined steps that allow other researchers to understand the process and the replicability of the results (Czakon, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic literature review was conducted to identify the current state of knowledge, evaluate the existing literature, and identify further research directions in the field of VIs. A previous (and only one, to the best of our knowledge) systematic literature review on the issue of CGIs and their use in the marketing field identified 32 scientific articles, of which only two referred to nonhuman VIs (da Silva et al, 2021). A systematic literature review follows well‐defined steps that allow other researchers to understand the process and the replicability of the results (Czakon, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…For a long time, stereotypes or fictional examples have existed in human society to represent the archetype of strength, beauty, and perfection that is not found in the average human being. Virtual influencers bring new scenarios to digital marketing and more; if most analyses point to more convergence than divergence between real and virtual and between human and non-human [2].…”
Section: Character Development and Creation Of Fictional Charactersmentioning
confidence: 99%
“…Today's technological advances have created worlds, games, and applications in which people can meet, talk, and socialize without physically being present. Individuals create virtual avatars, or representations of themselves, to represent the user in those environments [2]. Not only can the characters take on the form of people, but they can also take on the form of monsters, imaginative characters, and characters created by the creators.…”
Section: Introductionmentioning
confidence: 99%
“…The recent growth of ICTs has effectively reduced the distance between people across the globe with just a click. Such technological advancements enable people to access a wide array of services and online applications (e.g., e-learning/online teaching platforms, social networking sites or applications, online banking applications, and e-commerce applications, among others) using their smartphones and/or computers (Corcoran & Duane, 2018;da Silva Oliveira & Chimenti, 2021;Fernandes et al, 2021). ICTs thereby have emerged as an indispensable part of contemporary lifestyle, whereby individual personality effortlessly meshes with the fabric of human life, everyday situations, problems, and relationships (Alhassan et al, 2020;Donvito et al, 2020;Goyal et al, 2021;Soral et al, 2020).…”
Section: Introductionmentioning
confidence: 99%